Imperfect garden : the legacy of humanism - Todorov, Tzvetan, 1939-2017 (Princeton University Press, 2002)
Available in English for the first time, Imperfect Garden is both an approachable intellectual history and a bracing treatise on how we should understand and experience our lives. In it, one of France's most prominent intellectuals explores the foundations, limits, and possibilities of humanist thinking. Through his critical but sympathetic excavation of humanism, Tzvetan Todorov seeks an answer to modernity's fundamental challenge: how to maintain our hard-won liberty without paying too dearly in social ties, common values, and a coherent and responsible sense of self. Todorov reads afresh the.